Examining the Culture of Excellence (CoE) within a Private Philippine Higher Education Institution amidst of the Global Health Crisis - Andaya, Mitch; Buyco, Hamil; Cabo, Danica Chrizzy Ann; Dayrit, Rheal; Duenas, Jean; Espardinez, Weena Jennifer; Ferraro, John Bryan; Oriel, Margery; San Pedro, Jay R; Sucaldito, Shania Jane; Tan, Benjamin; Caballes, Dennis (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
Excellence is one of the thriving drives that any Higher Education Institution in Philippines to be attuned regardless of the challenges imposed by the society, especially during the initial phase of the global health crisis. The context of excellence in Higher Education has different vantage points that have great indicators or manifestations of being excellence in different foundational pillars of Higher Education Institutions. With this, the researchers examined the Culture of Excellence among the employees of a Private Philippine Higher Education Institution during the pandemic COVID-19 through a descriptive-correlational research design. Thus, the researchers developed and validated a research instrument that suited for the intention of the study. The developed research instrument was digitized and floated accordingly. Whereas, respondents were determined through the collaboration of the purposive and stratified sampling techniques. Afterward, the collected data was statistically analysed using frequency, percentage, weighted mean, standard deviation, and appropriate correlational analysis. It revealed that the respondents agree that they observed the indicators of Culture of Excellence despite of the global health crisis and modality of working. Furthermore, age and educational background were statistically related to their perception towards the Culture of Excellence. Based on these insights, the researchers created a proposed action plan to further harness and strengthen the said culture among the employees of the institution.